The influence of allergens on the development of selected ENT diseases in the pediatric population - Snoch, Olga; Kalinowska, Zuzanna; Ratajczak, Aleksandra; Matera, Weronika (Journal of Education, Health and Sport, 2024)
There is substantial evidence that allergies are a significant factor triggering and exacerbating many ENT diseases. The problem is particularly visible in the pediatric population, of which as many as 20% suffer from some form of atopy. Moreover, the course of these conditions is more complex than previously thought. The aim of the study was to collect information on the most common diseases in otorhinolaryngology and their link with hypersensitivity to allergens. The literature review included allergic rhinitis, adenoid hypertrophy, otitis media and sinusitis. Owing to a better understanding of the pathogenesis of these diseases, pediatricians can effectively treat and prevent their development.